THE APPLICATION OF PRESENTATION, PRACTICE, AND PRODUCTION (PPP) IN IMPROVING SPEAKING ABILITY OF THE ELEVENTH YEAR STUDENTS OF MAN 2 MODEL PALU - Zuhra, Zuhra (Fakultas tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Palu, 2016)
The aim of this research is to measure the effect of the application of presentation, Practice, and Production (PPP) of the eleventh year students of MAN 2 Model Palu. This pre-experimental research design took 27 students of the eleventh year students of MAN 2 Model Palu as the sample. They were chosen purposively. The instruments of data collection were observation, interview and oral. The students had limited ability in constructing present continuous tense. It can be seen in the result of mean score of pre-test (1,70). The data analysis showed that the ability of the students in pre-test was 1,70. It means that the speaking ability of the students in pre-test was very low. After the treatment their proficiency improved to be 3,12. It indicated that the speaking ability of the students after the treatment was higher than before the treatment. It means that PPP Method was effective in asking the Eleventh Year Students of Language Program of MAN 2 Model Palu in constructing present continuous tense sentences orally. After conducting the treatment, the researcher found that there was a significant difference between the mean value of the pre-test and post-test. It was proved that t-test value (7,51) was greater than the t-table value (2,05). It means that the use of PPP Method can improve the speaking ability of the Eleventh Year Students of Language Program Class of Man 2 Model Palu.